2011
DOI: 10.1074/jbc.m110.185793
|View full text |Cite
|
Sign up to set email alerts
|

Raftlin Is Involved in the Nucleocapture Complex to Induce Poly(I:C)-mediated TLR3 Activation

Abstract: The double-stranded RNA analog, poly(I:C), extracellularly activates both the endosomal Toll-like receptor (TLR) 3 and the cytoplasmic RNA helicase, melanoma differentiation-associated gene 5, leading to the production of type I interferons (IFNs) and inflammatory cytokines. The mechanism by which extracellular poly(I:C) is delivered to TLR3-positive organelles and the cytoplasm remains to be elucidated. Here, we show that the cytoplasmic lipid raft protein, Raftlin, is essential for poly(I:C) cellular uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 33 publications
2
72
0
Order By: Relevance
“…The features of the TLR3-recognizing PV-RNAs are consistent with our previous results that raftlin mediates poly(I:C) cellular uptake through interaction with the clathrin-AP-2 complex in human myeloid DCs and epithelial cells 35 . In addition, uptake of B/C-type CpG ODNs that share their uptake receptor with poly(I:C) was also mediated by raftlin 33,35 . Given that PV5-induced TLR3 activation in HEK293 cells was inhibited by pre-treatment with the B-type CpG ODN ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The features of the TLR3-recognizing PV-RNAs are consistent with our previous results that raftlin mediates poly(I:C) cellular uptake through interaction with the clathrin-AP-2 complex in human myeloid DCs and epithelial cells 35 . In addition, uptake of B/C-type CpG ODNs that share their uptake receptor with poly(I:C) was also mediated by raftlin 33,35 . Given that PV5-induced TLR3 activation in HEK293 cells was inhibited by pre-treatment with the B-type CpG ODN ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 79%
“…4c). The internalization of PV5 was similar to that of poly(I:C) 35 . Indeed, PV5 activity was inhibited by the pre-treatment of cells with B-type CpG oligodeoxynucleotide (ODN), which shares an uptake receptor with poly(I:C) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Recently, we have demonstrated that the cytoplasmic protein Raftlin is indispensable for cell entry of extracellular polyinosinic: polycytidylic acid [poly(I:C)], a virus dsRNA analogue, and TLR3-TICAM-1-mediated signaling (18). Raftlin was originally identified as a major raft protein with molecular mass of 63 kDa in B cells that colocalized with BCR in the lipid raft before and after BCR activation (19).…”
mentioning
confidence: 99%
“…Raftlin also localizes to the lipid raft in T cells and modulates BCR and TCR signaling (20). Although Raftlin possesses fatty acylation sites at the N terminus, it predominantly localizes in the cytoplasm in human epithelial cells and monocyte-derived DCs (Mo-DCs) (18,19). Upon poly(I:C) binding to the uptake receptor on the cell surface, Raftlin moves from the cytoplasm to the plasma membrane, where it induces endocytosis of the uptake receptor via interaction with the clathrin-clathrin-associated adaptor protein-2 (AP-2) complex.…”
mentioning
confidence: 99%